Mengintegrasikan Nilai-Nilai Buddhis dalam Penggunaan Media Sosial - Pedi; Willia Nando, Tedi (Jounal Nyanadassana, 2024)
This research aims to explore communication ethics in the use of social media, with a focus on Buddhist values ​​that can provide guidance for individuals in using social media. Ethics, as part of the moral values ​​implemented by religion, should be a guide for wise behavior, including when using social media. However, in reality, there is negligence in the use of social media in society, which involves practices such as smear campaigns, hate speech, online bullying (cyberbullying), and the spread of fake news (hoaxes). Therefore, this research is interesting to dig deeper through analysis of Buddhist values, so that Buddhist teachings can become a filter and guide for people to communicate wisely on social media. The research method used in this research is library research. Data analysis in this study highlights that social media use should reflect kindness, teachings of truth, joy, and consistency with facts. These four values ​​must be supported by other aspects, such as subtlety of language and expression, the basis of love in speaking, as well as consideration of the purpose and appropriate time in conveying the message. Manifestations can be found in content, writing or posts that have an educational, inspiring and useful character. In addition, when receiving information on social media, it is important to be selective and critical, but remain open to constructive criticism, while upholding healthy discussions on social media.